ANGGARAN PENDAPATAN DAN BELANJA NEGARA - Farum, La Ode (JIAR : Journal Of International Accounting Research, 2022)
This study aims to Know the Growth of Sources of State Revenues, Contributions from Sources of State Revenues, State Revenue Performance seen from Sources of State Revenues, and Efficient use of State Revenues and Expenditures. The benefits of this research are to provide information to readers about the state budget for income and expenditure, increase knowledge and information used in writing this research and can be a reference material that can provide a comparison in conducting research in the same field. The type of data used in this study is secondary data in the form of Time Series data. Secondary data is data obtained through prantara or media indirectly while time series data is a series of variable values ??at one time interval. This study uses descriptive quantitative analysis methods and ratio analysis. The results of this study state that revenues through taxes have contributed to the acceptance of the State, especially Domestic Tax revenues and use of the budget, are still very inefficient, because of the income or funding sources that are smaller than the expenditure made.